Application of Building Information Modeling in the Construction of the Parakan Lima Bridge in Purwakarta Regency - A M Aldo Hafiz Armandhy Firmansyah; Nurul Lastriana (Potensi: Jurnal Sipil Politeknik, 2025)
Parakan Lima Bridge was built by the Purwakarta Regency Government to improve transportation access. In this study, BIM was applied to the construction of the Parakan Lima Bridge by creating the bridge 3D model using Tekla Structures software, which can automatically generate the Quantity Take-Off of the project. The Quantity Take Off resulted from model were used as the basis for calculating the Cost Estimation Plan and project scheduling. The Cost Estimation Plan calculation was carried out by compiling the AHSP in Microsoft Excel, and the scheduling is created using Microsoft Project and Microsoft Excel software. The results of the 3D modeling, scheduling, and Cost Estimation Plan are then simulated in 4D and 5D using Navisworks software. To support the preparation of implementation methods and visualization during presentations, bridge animations are created using Sketchup and Lumion software, as well as Augmented Reality displays using Augin software. The result of this study shows that the cost estimate for the construction of the Parakan Lima Bridge was Rp 13,619,902,175 with an estimated project duration of 223 days, starting on May 23, 2022, and ended on December 31, 2022.